The Effect Of Mayo And Keto Diet and Physical Activities Toward Weight, Abdominal Circumference and Fat Thickness Reduction - Mis Ido Septian; Wara Kushartanti (Kazimierz Wielki University, 2019)
Aim: The aim of this research was for knowing and testing: 1) weight reduction after done the diet for 13 days; 2) the effect of mayo and keto diet towards consumer's physical activity; and 3) interaction between diet and physical activities. Methods: The reseach method that used is experimental with the use of 2x3 factorial design. Sample for this research was whole population which is 30 people of dandelion catering consumer, starting from junior high school students to house wives. The instrument used for measuring abdominal circumference was meter, for measuring weight was scale, and for measuring the fat thickness used skinfold. Analysis of this research was using ANOVA two paths with the score of significant level α= 0,05. Results: The result of this research is: 1) The effect of keto and mayo diet towards weight, waist circumference, and fat thickness reduction, in significant level of < α 0,05; 2) diet effect (mayo and keto) and physical activity toward weight, waist circumference, and fat thickness reduction, in sigficant score for weight 0.706 > α 0,05, for waist circumference 0.631 > α 0,05, and for fat thickness . 710 > α 0,05. Conclusion: The conclusion towards this reserach was: 1) there was a significant different effect between keto and mayo diet towards weight, waist circumference, and fat thickness reduction; 2) there was no different significant effect between diet (mayo and keto) and physical activity towards weight, waist circumference, and fat thickness reduction; and 3) there was no interaction between diet (keto and mayo) and activitiy (light, medium, high) towards weight, waist circumference, and fat thickness reduction.